Exclusive photoproduction of Υ{hooked} mesons at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Bellagamba, L; Boscherini, D; et al. (2009)
The exclusive photoproduction reaction γ p → Υ{hooked} p has been studied with the ZEUS experiment in ep collisions at HERA using an integrated luminosity of 468 pb -1. The measurement covers the kinematic range 60 < W < 220 GeV and Q 2 < 1   GeV 2, where W is the photon-proton centre-of-mass energy and Q 2 is the photon virtuality. These results, which represent the analysis of the full ZEUS data sample for this channel, are compared to predictions based on perturbative QCD. © 2009 Elsevier B.V.